The development of an objective wine knowledge scale: the item response theory approach. Issue 2 (15th June 2015) - Velikova, Natalia; Howell, Roy D.; Dodd, Tim
Abstract : Purpose: – The purpose of this paper is to address the issue of objective knowledge operationalisation with specific focus on varying levels of scale items' difficulty. The ultimate goal of the study was to develop a scale to measure objective wine knowledge, which would address the domain of wine knowledge and differentiate varying levels of consumer wine knowledge. Design/methodology/approach: – The process of items' development was guided by recommendations suggested by DeVellis (2003) in his influential work on theory and application of scale development. Examination of items' performance was conducted through a series of field tests with consumer samples ( N = 756) in a US wine region. Item response theory (IRT) approach was applied for items' testing. The developed items were analysed using the two-parameter logistic model in Mplus Version 5. Findings: – The study offers a 44-item test suitable for assessing wine knowledge across a broad spectrum of expertise. For example, if the goal is to assess wine knowledge differences among relatively knowledgeable respondents, a subset of more difficult items could be chosen. Alternatively, a test for novices could be constructed from easier scale's items. Research limitations/implications: – For researchers, the study offers conceptualisation of the wine knowledge domain, suggests a parsimonious instrument to measure the construct, offers a valid and reliable measure for use in testing theories of consumer knowledge and provides empirical evidence of the value and usefulness of the developed scale. Practical implications: – For professionals, the proposed test may be used to test consumer knowledge and to help assess a prospective employee's general knowledge of wine. The test can also be given at hospitality programs, outreach and continuing education programs. Originality/value: – The current paper takes an alternative approach to classical test theory and offers an objective wine knowledge scale tested through IRT. This approach avoids shortcomings associated with classical measurement and offers an original scale that can discriminate among respondents with different levels of wine knowledge.